Benign biliary neoplasms and biliary tumour precursors - Sarcognato, Samantha; Sacchi, Diana; Fassan, Matteo; Fabris, Luca; Cadamuro, Massimiliano; Zanus, Giacomo; Cataldo, Ivana; Covelli, Claudia; Capelli, Paola; Furlanetto, Alberto; Guido, Maria (Pathologica - Journal of the Italian Society of Anatomic Pathology and Diagnostic Cytopathology, 2021)
Benign biliary tumor are common lesions that are often an incidental finding in subjects who undergo medical imaging tests for other conditions. Most are true neoplasms while few result from reactive or malformative proliferation. Benign tumors have no clinical consequences, although the premalignant nature or potential for malignant transformation is of concern in some cases. The main practical problem for pathologists is the need to differentiate them from malignant biliary tumours, which is not always straightforward. Premalignant lesions of the bile duct have been described, although their incidence has been poorly characterized. These lesions include biliary mucinous cystic neoplasms, intraductal papillary neoplasms of the bile duct, and biliary intraepithelial neoplasia. In this article, histopathology of benign biliary tumors and biliary tumor precursors is discussed, with a focus on the main diagnostic criteria.